Exploratory Study on Wetlands Area Decrease in Bogotá due to Construction Activity: 1950-2016 - García-Ubaque, César Augusto; Ladino-Moreno, Edgar Orlando; Zamudio-Huertas, Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The aim of the study was to quantify in an explorative way the damage of the wetland area because of drying and construction activities from 1950 to 2016 in Bogotá city. To such end, an estimate of the wetland area of Bogotá was made for the years 1950, 1989 and 2016 by reviewing the geographic information of the Agustín Codazzi Geographical Institute (IGAC) and the Aqueduct and Sewer Bogotá Company (EAAB). The information was analyzed of the area variation for each water body. The data shows that the city's water mirror area has decreased by an average of 84.52% between the years of 1950, 1989 and 2016, except for El Tunjo wetland, which grew 79.45%. This situation shows that the protection that has been implemented happened too late, since a considerable portion of these ecosystems rich in fauna and flora is lost. This has generated phenomena such as: flooding of settlements in these areas, disappearance, or displacement of endemic species of flora and fauna and displacement of wetlands.